Penerapan Model Pembelajaran Project Based Learning Berpendekatan STEM untuk Mengembangkan Kecakapan Abad 21 Siswa dalam Pembelajaran Fisika - Suyanto, Suyanto (UNIVERSITAS INDRAPRASTA PGRI, 2023)
In 21st century learning, students are asked to improve their competencies to improve their ability to collaborate, think critically, communicate and think creatively. Teachers must be able to develop these 4 (four) skills in students so that they can keep up with current developments. One of them is developing students' 21st century skills with the Project Based Learning learning model with a STEM approach. The research method uses a quasi-experimental method with an